Fluorinated acrylic monomer modified core-shell polyacrylate latex particles: Preparation, properties and characterizations. (28th April 2022) - Zhang, Fuhao; Jing, Cheng; Yan, Zhangyin; Ge, Shengsong; Liu, Ping; Maganti, Srihari; Xu, Ben Bin; Mahmoud, Khaled H.; El-Bahy, Zeinhom M.; Huang, Mina; Guo, Zhanhu
Abstract: The core-shell acrylic emulsion was synthesized by a semicontinuous seeded emulsion polymerization with acrylate monomers as the main materials and octafluoropentyl methacrylate (OFPMA) as modified monomers. The influences of OFPMA on the hydrophobicity, thermal stability and mechanical properties of acrylic latex film were investigated. Fourier transform infrared spectroscopy (FTIR) analysis and X-ray photoelectron spectroscopy (XPS) indicated that the OFPMA was successfully incorporated into the acrylic resin chain. Transmission electron microscope (TEM) image showed a core-shell structure of the emulsion particles. The addition of OFPMA reduced the water absorption ratio (3.2 wt%) of the latex film and improved its water resistance. Contact angle of coating film surface increased from 80.7° to 90.7°. Moreover, TGA curves showed that the addition of OFPMA increased the initial decomposition temperature of the polymer from 355 to 370 °C. Additionally, with the addition of OFPMA, the tensile strength of modified polymers was also improved to 7.77 MPa compared to pure acrylic resin. The application of the core-shell structure can reduce the amount of fluorine-containing acrylic monomers and environmental pollution, and improve economic benefits. This study provides a new kind of environmentally friendly waterborne acrylic resin and a simple method for optimizing the performance of waterborne resins. Graphical abstract: Image 1 Highlights: The core-shell acrylic emulsion modified by octafluoropentyl methacrylate was synthesized via a semicontinuous seeded emulsion polymerization. The core-shell acrylic emulsion exhibited excellent water resistance and thermal stability. The core-shell structure reduces the amount of fluorine-containing acrylic monomers.